2008
DOI: 10.1186/1471-2164-9-575
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiling of components associated with exoskeletal hardening in crustaceans

Abstract: Background: Exoskeletal hardening in crustaceans can be attributed to mineralization and sclerotization of the organic matrix. Glycoproteins have been implicated in the calcification process of many matrices. Sclerotization, on the other hand, is catalysed by phenoloxidases, which also play a role in melanization and the immunological response in arthropods. Custom cDNA microarrays from Portunus pelagicus were used to identify genes possibly associated with the activation pathways involved in these processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 57 publications
2
39
1
1
Order By: Relevance
“…S3). This is in agreement with the results presented by Kuballa and Elizur (2008) that a Pl-MBL homologue is highly upregulated in the crab Portunus pelagicus at post molt. Taken together, these results indicate a role for Pl-MBL in calcification of a new cuticle during molting, and in addition the LPS binding properties of this protein may be important in regulation of the proPO system during sclerotization and to prevent spreading of LPS or bacteria in the hemolymph during the sensitive molting stage.…”
Section: Fig 8 Propo Activation In Hls Is Dependent Of Cacl2 (A)supporting
confidence: 94%
“…S3). This is in agreement with the results presented by Kuballa and Elizur (2008) that a Pl-MBL homologue is highly upregulated in the crab Portunus pelagicus at post molt. Taken together, these results indicate a role for Pl-MBL in calcification of a new cuticle during molting, and in addition the LPS binding properties of this protein may be important in regulation of the proPO system during sclerotization and to prevent spreading of LPS or bacteria in the hemolymph during the sensitive molting stage.…”
Section: Fig 8 Propo Activation In Hls Is Dependent Of Cacl2 (A)supporting
confidence: 94%
“…In nature, crustacean animals periodically undergo cyclic molt of the exoskeleton, which is essential for their growth, metamorphosis, and reproduction (14)(15)(16). Armadillidium vulgare belongs to terrestrial-dwelling crustacean taxon isopod.…”
mentioning
confidence: 99%
“…In an earlier work, Terwilliger and colleagues (Terwilliger et al, 2005) showed in juvenile crabs that the hemolymph concentration of hemocyanin cyclically decreased at ecdysis, and increased as pre-molt progressed until the next molt event. At the transcript level, hemocyanins of the crab Portunus pelagicus showed high levels of expression in the intermolt and pre-molt stages, when compared with ecdysis and postmolt (Kuballa and Elizur, 2008;Kuballa et al, 2011). In C. quadricarinatus, a microarray experiment comparing hepatopancreas gene expression in inter-molt versus pre-molt and post-molt animals indicated a reduction in the transcription levels of one hemocyanin gene in inter-molt, while another hemocyanin gene was most highly transcribed in inter-molt .…”
Section: The Journal Of Experimental Biology 216 (10)mentioning
confidence: 99%
“…These microfibrils form a network of chitin-protein layers that are helicoidally stacked into a twisted plywood pattern (Bouligand, 1972;Raabe et al, 2005). The rigidity of the exoskeleton is achieved through sclerotization, namely the enzymatic oxidation of phenols or catechols, which then crosslink with and harden cuticular proteins and chitin (Kuballa and Elizur, 2008). In most crustacean species, exoskeletons are further hardened by the deposition of minerals, mainly calcium carbonate (Lowenstam and Weiner, 1989).…”
Section: Introductionmentioning
confidence: 99%